2016
DOI: 10.1080/13548506.2016.1164872
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of hopelessness and suicidal behavior in the city of Athens, Greece. The role of the financial crisis

Abstract: This study aimed to examine the psychometric properties of Beck Hopelessness Scale (BHS) in Greek patients with a recent suicide attempt, the predictive ability of BHS especially in terms of age and the possible effect of the financial crisis on hopelessness as it has been identified as a significant suicide risk factor. The study included a total of 510 individuals, citizens of Athens, Greece. Three hundred and forty individuals (170 attempted suicide patients, and 170 -age and gender- matched healthy individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
6
0
4
Order By: Relevance
“…Income inequality and personal economic distress has been associated with an increased risk of SI and attempts in South Korea and Greece [ 30 , 47 , 52 ]. Studies in Europe found that in the post-recession period people at higher risk of SI and attempt were unemployed, had financial hardship, low interpersonal trust, were married (53 times greater risk than unmarried), perceived a negative impact of the GFC, and had a history of suicide attempt (14.41 times risk) or MDD (97 times greater risk) [ 27 , 52 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The median age of people who attempt suicide increased following the GFC to middle-aged adults, particularly those approaching retirement [ 74 , 75 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Income inequality and personal economic distress has been associated with an increased risk of SI and attempts in South Korea and Greece [ 30 , 47 , 52 ]. Studies in Europe found that in the post-recession period people at higher risk of SI and attempt were unemployed, had financial hardship, low interpersonal trust, were married (53 times greater risk than unmarried), perceived a negative impact of the GFC, and had a history of suicide attempt (14.41 times risk) or MDD (97 times greater risk) [ 27 , 52 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. The median age of people who attempt suicide increased following the GFC to middle-aged adults, particularly those approaching retirement [ 74 , 75 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Health Geographics negative health consequences in the Greek population have been connected to perceived diminishing health, and increased prevalence rates of mental health problems including depression [4,5]. Additionally, an increase in suicide rates has been recorded [6], and suicide attempts have been associated to increased hopelessness [7]. During the years of economic crisis in Greece it was found that young Greek adults reported higher perceived stress but had lower physiological stress than comparable young adults in Sweden [8].…”
Section: Open Accessmentioning
confidence: 99%
“…Syndromes have been described for those societies that use certain production systems, for example temporary reversal of roles in agricultural societies, mass-trance, ghost possession syndrome of ancestors, and industrial disease. Societies that are experiencing rapid economic crises or decline have a higher level of distress in their populations, which has led to an increase in suicide rates (Christodoulou et al, 2017;Mattei, Pistoresi, & Vogli, 2019), depression, alcohol abuse, and gambling.…”
Section: Panorama Of Mutating Syndromes (Cybernetics Of the Syndromes)mentioning
confidence: 99%